Insertable cardiac monitors after cryptogenic stroke – a risk factor based approach to enhance the detection rate for paroxysmal atrial fibrillation. (16th October 2015) - Poli, S.; Diedler, J.; Härtig, F.; Götz, N.; Bauer, A.; Sachse, T.; Müller, K.; Müller, I.; Stimpfle, F.; Duckheim, M.; Steeg, M.; Eick, C.; et al.
Abstract : Background and purpose: Recently, the CRYSTAL AF trial detected paroxysmal atrial fibrillation (AF) in 12.4% of patients after cryptogenic ischaemic stroke (IS) or cryptogenic transient ischaemic attack (TIA) by an insertable cardiac monitor (ICM) within 1 year of monitoring. Our aim was (i) to assess if an AF risk factor based pre‐selection of ICM candidates would enhance the rate of AF detection and (ii) to determine AF risk factors with significant predictive value for AF detection. Methods: Seventy‐five patients with cryptogenic IS/TIA were consecutively enrolled if at least one of the following AF risk factors was present: a CHA2 DS2 ‐VASc score ≥4, atrial runs, left atrium (LA) size >45 mm, left atrial appendage (LAA) flow ≤0.2 m/s, or spontaneous echo contrast in the LAA. The electrocardiographic and echocardiographic criteria were chosen as they have been repeatedly reported to predict AF; the same applies for four of the six items of the CHA2 DS2 ‐VASc score. The study end‐point was the detection of one or more episodes of AF (≥2 min). Results: Seventy‐four patients underwent implantation of an ICM; one patient had AF at the date of implantation. After 6 months, AF was detected in 21/75 patients (28%), after 12 months in 25/75 patients (33.3%). 92% of AF episodes were asymptomatic. LA size >45 mm and the presence of atrial runs were independently associated with AF detection [hazard ratio 3.6 (95% confidence interval 1.6–8.4), P = 0.002, and 2.7 (1.2–6.7), P = 0.023, respectively]. Conclusions: The detection rate of AF is one‐third after 1 year if candidates for an ICM after cryptogenic IS/TIA are selected by AF risk factors. LA dilation and atrial runs independently predict AF. Abstract : Clickhere to view the accompanying paper in this issue.